Recovery of benthic communities from small-scale shrimp trawling: Evidence from using ecological indices over a short temporal scale. (April 2019) - Rabaoui, Lotfi; Lin, Yu-Jia; Roa-Ureta, Rubén H.; Dagoy, Joshua; Joydas, Thadickal V.; Borja, Angel; Muxika, Iñigo; Franco, Javier; Al-Abdulkader, Khaled; Loughland, Ronald; Alnazry, Hussein; Qurban, Mohammed A.
Highlights: The effect of shrimp trawling on the Arabian Gulf benthic communities was assessed. Both seasonal and immediate effect methodologies showed an evident trawling effect. No significant effect on the sediment texture was found. The seasonal study revealed a cyclic dynamics of the benthic assemblages. The shrimp-season impact on benthos is reverted during the trawl ban season. Abstract: Mobile fishing gears are responsible of various direct effects on benthic communities. The most important (in volume and value) fishery in Saudi waters of the Arabian Gulf is the 6-month trawl season for the green tiger shrimp. The fleet is composed of hundreds of artisanal boats carrying out short-duration tows of small trawls. To study the impact of this trawl season on local benthic communities, two different methodologies were adopted in three areas of different trawling intensities. The first study design was aimed at the seasonal effect and the second design examined the immediate impact after the pass of a trawl. Both studies were evaluated using univariate ecological indicators (richness, diversity, AMBI, M-AMBI) and the multivariate species composition. The seasonal study revealed a cyclic dynamics of the benthic assemblages. Most of the univariate ecological descriptors decreased during the trawling season and increased during the off-season while species composition undertook a round trip in multivariate space, thus supporting the conclusion that the impact of trawling on the benthic ecosystem during the shrimp season is reverted during the trawl ban. Although our results confirm predictions of synthetic statistical models, they also show that the impact of trawling on benthic communities strongly depend on the existence of a trawl ban period.